Flexible strain sensors with rapid self-healing by multiple hydrogen bonds. (12th August 2020) - Liu, Li; Li, Xinhe; Ren, Xiuyan; Wu, Guang feng
Abstract: Hydrogels have been applied in flexible strain sensors due to good conductivity, stretchability and sensitivity to strain. However, gaining rapid and effective self-healing hydrogels for the durability of flexible strain sensors is still a challenging. Herein, we report a tough, conductive hydrogel that can rapidly self-healing at room temperature. The hydrogel is fabricated by incorporating polystyrene-co-poly ( N, N -dimethylacrylamide) (P (St-co-DMAA)) microspheres prepared by emulsion polymerization into hydrophobic association hydrogels networks composed of polyacrylamide-co-poly (hexadecyl methacrylate) (PAAm-co-PHMA), sodium dodecyl sulfate (SDS) and sodium chloride (NaCl). The hydrogel possesses a dual dynamic crosslinking comprising of multiple hydrogen bonds and hydrophobic association. The multiple hydrogen bonds formed between the outer regions of microspheres and PAAm chains provide rapid self-healing of hydrogels and contribute to re-association of hydrophobic chains and further improve self-healing efficiency. (99% Self-healing efficiency at room temperature for 2 h). At the same time, the dual crosslinking also gives the hydrogel good mechanical properties and fatigue resistance. In addition, the existence of sodium ions and chloride ions also endowed the hydrogel high sensitive deformation-dependent conductivity, make the hydrogel able to sensitive sensing of large and small strain signals (e.g. finger bending and breathing). And the sensing ability of hydrogel can be also recovered quickly after self-healing. Therefore, this strategy will expand the application range of a new generation of hydrogels such as self-healing conductors, robotic electronic skin and strain sensors, etc. Graphical abstract: Image 1 Highlights: Multiple hydrogen bonds give hydrogels rapid self-healing properties. The hydrogels exhibited tough and fatigue resistance and self-recoverability. The existence of sodium and chloride ions endowed the hydrogel conductivity. The strain sensing ability of hydrogel can be recovered quickly after self-healing.